2011
DOI: 10.1002/cbic.201100306
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Crowding of Ribosomes and Proteins inside Vesicles: A Possible Mechanism for the Origin of Cell Metabolism

Abstract: One of the open questions in the origin of life is the spontaneous formation of primitive cell-like compartments from free molecules in solution and membranes. "Metabolism-first" and "replicator-first" theories claim that early catalytic cycles first evolved in solution, and became encapsulated inside lipid vesicles later on. "Compartment-first" theories suggest that metabolism progressively occurred inside compartments. Both views have some weaknesses: the low probability of co-entrapment of several compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 19 publications
4
54
0
Order By: Relevance
“…In this case, where multiple co-encapsulation events occur, the "anomalous entrapment" phenomenon (seen before for single molecular species [13,19]) acts by creating nanoscale liposomes containing hundreds of different molecules in a very small volume.…”
Section: General Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…In this case, where multiple co-encapsulation events occur, the "anomalous entrapment" phenomenon (seen before for single molecular species [13,19]) acts by creating nanoscale liposomes containing hundreds of different molecules in a very small volume.…”
Section: General Strategymentioning
confidence: 97%
“…It is more difficult to perform similar studies in submicron vesicles, where it is expected, however, a higher diversity due to the enhancement of stochastic events at a smaller scale. Quite interestingly, two recent studies demonstrated that when 200 nm (diameter) lipid vesicles are prepared in presence of single macromolecular species, like ferritin [13] or ribosomes [14], the solute encapsulation does not follow the expected behavior. It resulted, instead, in a dramatic dichotomy between many "empty" vesicles and few "super-crowded" ones (having an internal solute concentration up to 60 times higher than the expected value).…”
Section: The Encapsulation Of Solutes Inside Lipid Vesiclesmentioning
confidence: 99%
“…The reconstitution of transcription-translation machinery from fully defined components 9 inside of vesicles 28 was particularly significant in facilitating later efforts in constructing environmentally responsive artificial cells17,18. Similarly, artificial cell studies have been used to probe evolutionary processes 4,29,30 , the mechanistic details of RNA and protein synthesis 22,31 , the influences of metabolic load32,33, and the assembly of viral particles 34 . Importantly, enough knowledge now exists that basic cellular function can be reconstituted inside of vesicles in the laboratory following these previous reports and the protocols described herein.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it should be recalled that studies have shown that molecular crowding, which has been found in some vesicle systems [106,107,108], favors reverse proteolysis by volume exclusion effects [109]. The lipid membrane can favor growing reactions only inside the liposome lumen, owing to its semi-permeability, and provides a matrix for the peptide formation at the same time [110].…”
Section: A Peptide “Fragment Condensation” Scenariomentioning
confidence: 99%